Hubungan Dukungan Orang Tua dan Regulasi Diri dengan Tanggung Jawab Belajar pada Siswa Sekolah Menengah Atas Negeri 1 Lhokseumawe - T. Isman Surdi; Sri Milfayetty; Masganti Masganti (Mahesa Research Center, 2022)
This study aims to determine the relationship between parental support and self regulation with learning responsbilitiies in SMA Negeri 1 Lhokseumawe students. The research approach is quantitative with the type of correlational research. The population of this research is the student of class XI SMA Negeri 1 Lhokseumawe, totaling 330 student. The research sample used the Slovin formula with a sample size of 181 people. The independent variables in this study were parental support and self regulation, while the dependent variable was learning responsibility. The research was carried out at SMA Negeri 1 Lhokseumawe in november 2021. The research data collection technique used a scale. The data analysis technique used the statistical test of the SPSS 26 program. Based of the results of the Pearson correlation calculation, the results of the relationship between parental support and learning responsibility rx1y were 0.379 and the relationship between self regulation and learning responsibility rx2y was 0.387. The results of multiple regression analysis show that the F test count 18.985 > F table 3.046, accept Ha reject H0 that is, there is a simultaneous relationship between parental support, self regulation and learning responsibilies in SMA Negeri 1 Lhokseumawe student rx1,2y of 0.419. it can be concluded that there is a relationship between parental support and self regulation of 41.9% on student learning responsibilities. It is recomended for parents to pay attention and support their children. Furthermore, students of SMA Negeri 1 Lhokseumawe can organize themselves and be responsible for laerning.